Design of buried flexible pipelines during liquefaction - Prasad Valleti, Durga; Sathyam, Neelima; Sivaranjani, S.; Shahin, C.; Mondal, Sneha (International Journal of Engineering and Technology, 2018)
Pipelines are important facilities over the huge area to encounter a seismic hazards and conditions of soil. In India pipe lines run through high seismic areas and exposed to considerable risk. The pipelines have advanced in India compare through the world scenario there is no uniform guideline available for seismic design. Therefore we need to establish at least degree of safety for standard seismic design of pipelines. As a part of this, a number of flexible pipelines of different diameter, length, and thickness have been taken into consideration. The density, internal pressure and density of surrounding soil are taken into account and is checked against permanent ground deformation (PGD) due to liquefaction. Using ABAQUS SOFTWARE we will analyse the soil pipeline interaction and based on the results obtained some consideration are given for the design of pipeline in the Liquefied zone, which improve the capability of the pipeline to withstand buoyancy force due to soil liquefaction. The safety of buried pipelines is analyzed as per IITK-GSDMA (IIT-Kanpur-Gujarat state Disaster Management Authority) guidelines on seismic design.